Management accounting in service industry. - Chia, Mei Hua. (2008)
This study is done with the purpose of evaluating management accounting techniques adopted by service industry in Singapore. As the adoption of management accounting techniques largely depends on the nature of the business. Therefore, we hope to find out the underlying reasons of adopting certain management accounting techniques in service industry.